Exoskeleton gait training on real-world terrain improves spatiotemporal performance in cerebral palsy - Tagoe, Emmanuella A.; Fang, Ying; Williams, Jack R.; Stone, Julie L.; Lerner, Zachary F. (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction Walking is essential for daily life but poses a significant challenge for many individuals with neurological conditions like cerebral palsy (CP), which is the leading cause of childhood walking disability. Although lower-limb exoskeletons show promise in improving walking ability in laboratory and controlled overground settings, it remains unknown whether these benefits translate to real-world environments, where they could have the greatest impact. Methods This feasibility study evaluated whether an untethered ankle exoskeleton with an adaptable controller can improve spatiotemporal outcomes in eight individuals with CP after low-frequency exoskeleton-assisted gait training on real-world terrain. Results Comparing post- and pre-assessment, assisted walking speed increased by 11% and cadence by 7% (p = 0.003; p = 0.006), while unassisted walking speed increased by 8% and cadence by 5% (p = 0.009; p = 0.012). In the post-assessment, assisted walking speed increased by 9% and stride length by 8% relative to unassisted walking (p < 0.001; p < 0.001). Improvements in walking speed were more strongly associated with longer strides than higher cadence (R2 = 0.92; R2 = 0.68). Muscle activity outcomes, including co-contraction of the soleus and tibialis anterior, did not significantly change after training. Discussion These findings highlight the spatiotemporal benefits of an adaptive ankle exoskeleton for individuals with CP in real-world settings after short-term training. This work paves the way for future randomized controlled trials (RCTs) to evaluate the isolated effects of adaptive ankle exoskeletons on gait performance and neuromuscular outcomes in individuals with CP in real-world environments